2012
DOI: 10.1186/1471-2202-13-95
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone regulation of sex steroid-related mRNAs and dopamine-related mRNAs in adolescent male rat substantia nigra

Abstract: BackgroundIncreased risk of schizophrenia in adolescent males indicates that a link between the development of dopamine-related psychopathology and testosterone-driven brain changes may exist. However, contradictions as to whether testosterone increases or decreases dopamine neurotransmission are found and most studies address this in adult animals. Testosterone-dependent actions in neurons are direct via activation of androgen receptors (AR) or indirect by conversion to 17β-estradiol and activation of estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 56 publications
(68 reference statements)
7
90
2
1
Order By: Relevance
“…The relationship with testosterone in the healthy men is consistent with the sex steroid modulation of reward prediction-error signals in the ventral striatum and may reflect changes in dopamine signaling. We also detected testosterone receptors (AR) in the human midbrain consistent with the direct modulation of dopamine by sex steroids and thus, dopamine neurons could be mediators of the testosterone-related changes we observed in the ventral striatum BOLD signal which is also supported by findings of testosterone directly regulating dopamine related gene expression in male rodents (Purves-Tyson et al, 2012). In addition, in post mortem human male substantia nigra we showed that tyrosine hydroxylase gene expression, an indicator of dopamine synthesis capacity, was positively (B) regions of a significant two-way interaction between group, i.e., HM N men with schizophrenia (SZ), neural activity and testosterone levels in the striatum; (C) the significant correlation between the BOLD parameter estimates (UR N ER) and testosterone at the peak voxel in HM; and (D) the negative (and non-significant) correlation between BOLD parameter estimates (UR N ER) and testosterone in SZ, confirming the significant two-way interaction in B was due to a weaker or reversed effect among SZ.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The relationship with testosterone in the healthy men is consistent with the sex steroid modulation of reward prediction-error signals in the ventral striatum and may reflect changes in dopamine signaling. We also detected testosterone receptors (AR) in the human midbrain consistent with the direct modulation of dopamine by sex steroids and thus, dopamine neurons could be mediators of the testosterone-related changes we observed in the ventral striatum BOLD signal which is also supported by findings of testosterone directly regulating dopamine related gene expression in male rodents (Purves-Tyson et al, 2012). In addition, in post mortem human male substantia nigra we showed that tyrosine hydroxylase gene expression, an indicator of dopamine synthesis capacity, was positively (B) regions of a significant two-way interaction between group, i.e., HM N men with schizophrenia (SZ), neural activity and testosterone levels in the striatum; (C) the significant correlation between the BOLD parameter estimates (UR N ER) and testosterone at the peak voxel in HM; and (D) the negative (and non-significant) correlation between BOLD parameter estimates (UR N ER) and testosterone in SZ, confirming the significant two-way interaction in B was due to a weaker or reversed effect among SZ.…”
Section: Discussionsupporting
confidence: 81%
“…In particular, we have found that circulating testosterone levels in adolescent male rhesus macaques correlate with dopamine synthesis potential, as inferred from increased striatal tyrosine hydroxylase levels -the rate-limiting step in dopamine biosynthesis (Morris et al, 2010). Our studies in rodents also find that testosterone triggers a positive feedback loop to change the level of dopamine receptors and breakdown enzymes and dopamine transporters via AR action (Purves-Tyson et al, 2012. Our current study of human post mortem substantia nigra in patients and controls also found a positive association between a potential functional expression of AR and tyrosine hydroxylase.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…During adolescence, testosterone and estrogen influence brain maturation/development in dopaminergic regions including the striatum and prefrontal cortex, and also have a significant role in shaping the dopaminergic signal (Andersen 2003;Purves-Tyson et al 2012;Sinclair et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We reported that increasing testosterone over the male adolescent period (postnatal day [PND] 45-60) resulted in an increase in dopamine synthesis potential (tyrosine hydroxylase [TH] protein expression) in the young adult substantia nigra (Purves-Tyson et al, 2012) but not in the striatum (Purves-Tyson et al, 2014), but also found in late adolescent rhesus macaques that circulating testosterone levels correlated with TH levels in the putamen (Morris et al, 2010). We also reported, in young adult rats, that increasing testosterone over the adolescent period increased dopamine receptor D2 (DRD2) gene expression in both the substantia nigra and dorsal striatum (Purves-Tyson et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%